Virtual Screening - Taha, Mutasem O. (IntechOpen, 2012)
Pharmacophore modeling, QSAR analysis, CoMFA, CoMSIA, docking and molecular dynamics simulations, are currently implemented to varying degrees in virtual screening towards discovery of new bioactive hits. Implementation of such techniques requires multidisciplinary knowledge and experience. This volume discusses established methodologies as well as new trends in virtual screening with aim of facilitating their use in drug discovery.